Compatibility of Trichoderma harzianum with Different Concentrations of Copper Oxychloride Fungicide (International Journal of Food and Nutritional Sciences, 2023)
Trichoderma harzianum is a widely used biocontrol agent known for its antagonistic activity against various plant pathogens. Copper oxychloride is a common fungicide used to combat fungal diseases in agriculture. The present research aims to investigate the compatibility of Trichoderma harzianum with different concentrations of copper oxychloride fungicide. The study was conducted to assess the potential impact different concentrations of copper oxychloride viz., 200 ppm, 400 ppm, 600 ppm, 800 ppm and 1000 ppm on the growth, survival, and antagonistic capabilities of Trichoderma harzianum. The results obtained from this research can provide valuable insights into the feasibility of integrating Trichoderma harzianum with copper oxychloride for sustainable and effective disease management in agriculture.